ECO ELECTRODE, ELECTRICAL ENERGY STORAGE DEVICE, AND METHOD FOR MANUFACTURING SAME

JP7608371B2Active Publication Date: 2025-01-06TOTALENERGIES ONETECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021571843
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-03
Filing Date
2020-06-03
Publication Date
2025-01-06
Estimated Expiration
2040-06-03

Smart Images

  • Figure 0007608371000001
    Figure 0007608371000001
  • Figure 0007608371000002
    Figure 0007608371000002
  • Figure 0007608371000003
    Figure 0007608371000003
Patent Text Reader

Abstract

Eco-electrode, electrical energy storage device, and method for making same. The present invention relates to a composite electrode for an electrical energy storage device, the electrode comprising an electrode body and an electrode shell, the body comprising at least one water-soluble polymer, and at least a portion of the shell comprising at least one organic or organometallic material. The present invention also relates to an electrical energy storage device comprising the composite electrode and a method for making the composite electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite electrode for electrical energy storage devices, including for example batteries and capacitors, such as electrochemical double layer capacitors (ultracapacitors). The present invention also relates to an electrical energy storage device comprising said composite electrode, and to a method for making said composite electrode. [Background technology]

[0002] Many of the batteries and capacitors can be considered as harmful to the environment. For some specific applications, but also for a better future, it would be important to have environmentally friendly or biodegradable electrical energy storage devices. Batteries are made of several materials (active materials, polymeric binders, metal current collectors, etc.), which need to be overhauled if we want to have devices that are more compatible with the environment. The binders are generally fluoropolymers whatever the battery electrolyte (aqueous or organic medium).

[0003] Water-soluble polymers (CMC, PAA, etc.) are increasingly being considered as binders for potential electrodes that must work in organic electrolytes. The electrodes can be formulated in water, which is an important advantage from a process point of view.

[0004] Of course, such polymers cannot be used as electrode binders for aqueous batteries due to their water solubility. The use of binders that dissolve in aqueous solvents, such as bio-based CMC (carboxymethylcellulose) and other binders such as PEO (polyethylene oxide), PVA (polyvinyl alcohol), PLA (polylactic acid), etc., prevents the use of these electrodes with aqueous electrolytes. In fact, when electrodes with water-soluble binders are placed in contact with an aqueous electrolyte, the strong chemical interaction between water and the binder causes an electron permeation loss of the electrode due to dissolution of the electrode. This narrows the scope of application of this type of composite electrode binder for use in the field of "green" batteries. In this context, it would be advantageous economically and in terms of environmental protection if electrodes based on water-soluble binders, such as CMC and other binders, could be used in aqueous batteries. As a result, to date, bio-based polymers such as CMC, HPMC (hydroxypropyl methylcellulose), etc., cannot be used as electrode binders in aqueous batteries.

[0005] The manufacture of a typical composite electrode for a battery (such as a lithium-ion battery) consists of mixing the active material, which is deposited on a current collector, with carbon black and with a binder. In the case of ultracapacitors, the active material is porous carbon. The binder is dissolved in a solvent before the mixture is made. A typical binder used is polyvinylidene fluoride (PVDF) dissolved in N-methylpyrrolidone (NMP). Other binder and solvent combinations are also possible. The electrochemical stability and compatibility of the binder with the working environment in the potential range of interest should also be taken into account. PVDF does not adapt well to aqueous media. In this context, it would be very advantageous if composite electrodes based on bio-derived binders could be used in aqueous batteries, since the materials and methods for making industrial electrodes would not change. Moreover, the organic solvents commonly used are harmful, volatile and flammable. In this context, the use of binders that dissolve in aqueous solvents therefore has three advantages:

[0006] So far, physicochemical treatments in the battery electrode field have been mainly performed on active material particles to modify the chemical interfaces.

[0007] Extensive efforts have been made to cover the active material (nanoparticles) before fabricating the composite electrode. The only existing examples of direct deposition on composite electrodes involve oxide deposition (typically Al) to reduce uncontrolled dissolution of electroactive products and formation of secondary products in organic electrolyte batteries. 2 O 3 ) (U.S. Patent Application Publication No. 2012 / 0077082).

[0008] Furthermore, the prior art has focused primarily on cells operating in organic media. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] US Patent Application Publication No. 2012 / 0077082 Summary of the Invention [Problem to be solved by the invention]

[0010] [Objective of the Invention] The present invention seeks to overcome the technical problems of providing composite electrodes for electrical energy storage devices.

[0011] The present invention seeks to overcome the technical problems of providing a composite electrode for an electrical energy storage device that works with an aqueous electrolyte.

[0012] The present invention seeks to overcome the technical problem of providing a composite electrode for an electrical energy storage device working in contact with an aqueous medium.

[0013] The present invention aims to overcome the technical problems of providing an electrical energy storage device having such composite electrodes.

[0014] The present invention aims to overcome the technical problem of providing a method for making such composite electrodes.

[0015] The present invention aims inter alia to provide such a method at low cost.

[0016] The present invention aims inter alia to overcome the technical problem of providing a method for producing electrical energy storage devices and / or composite electrodes while integrating the industrial process for producing such composite electrodes without modifying other process steps.

[0017] The present invention seeks to overcome the technical problem of providing a method for adapting composite electrodes comprising water-soluble binders to electrical energy storage devices working in aqueous media and / or with aqueous or organic electrolytes.

[0018] The present invention seeks to overcome the above mentioned technical problems whilst being an environmentally friendly or "green" qualified method or electrical energy storage device. [Means for solving the problem]

[0019] [Description of the Invention] The present invention relates to a composite electrode for an electrical energy storage device and to a method for preparing such a composite electrode by plasma treatment, in particular to improve its electrochemical behavior.

[0020] The present invention relates to a composite electrode for an electrical energy storage device, the electrode comprising an electrode body and an electrode shell, the body comprising at least one water-soluble polymer and at least a portion of the shell comprising at least one organic or organometallic material.

[0021] A composite electrode according to the present invention comprises one or more binders that comprise a water-soluble polymer.

[0022] In one embodiment, the water soluble polymer is a bio-derived polymer.

[0023] In one embodiment, the water soluble polymer is selected from the group consisting of polysaccharides, polyethylene glycol (PEG), polyoxyethylene (POE), polyvinylpyrrolidone (PVP), polyvinyl alcohol (PVA), polylactic acid (PLA), polyacrylic acid (PAA), polyacrylamide, N-(2-hydroxypropyl) methacrylamide (HPMA), cellulose derivatives, especially alkylcelluloses, dialkylcelluloses, hydroxyalkylcelluloses, hydroxyalkylalkylcelluloses, carboxyalkylcelluloses, pectin, chitosan, chitosan derivatives, dextran, carrageenan, guar gum, guar gum derivatives, especially hydroxypropyl guar, carboxyalkyl guar, hyaluronic acid (HA), starch or starch derivatives, polyethyloxazoline, and derivatives thereof.

[0024] In one embodiment, the water soluble polymer is selected from the group consisting of hydroxypropyl methylcellulose (HPMC), hydroxypropyl cellulose (HPC), hydroxyethyl cellulose (HEC), carboxymethyl cellulose (CMC), especially sodium carboxymethyl cellulose (Na-CMC).

[0025] Examples of water-soluble polymers include polyethylene oxide (PEO, eg, PEO from 100,000 g / mol up to several million g / mol, typically up to 1.5 million g / mol).

[0026] The present invention makes it possible to use bio-derived polymers, and more generally water-soluble polymers, as electrode binders for composite electrodes for electrical energy storage devices.

[0027] Linking aqueous electrolytes to bio-based polymer binders is a very promising step towards developing more environmentally friendly electrical energy storage devices.

[0028] The use of water-soluble polymers as binders, especially in composite electrodes, has great technical advantages, especially in terms of the environment, safety and manufacturing costs, especially for the fabrication of electrical energy storage devices.

[0029] Typically, water-soluble polymers are used as binders for the electrodes, allowing composite electrodes of this type to be used in aqueous as well as organic electrolytes.

[0030] The use of water-soluble polymers, and especially CMC, as binders for electrode fabrication is an economic and environmental breakthrough.

[0031] The method for determining whether a polymer is water soluble is as follows. 1-5% by weight of the polymer is placed and stirred in a closed vial containing 95-99% by weight of water. A clear solution is observed after at least 2 days when no traces of undissolved polymer can be observed anymore.

[0032] The composite electrode containing a polymer (water-soluble polymer) as a binder is weighed to determine the exact amount of composite compound relative to the weight of the current collector that constitutes the electrode. The composite compound is composed of approximately 85-90% by weight of active material, 5-10% by weight of carbon black (C65, Timcal) and 5-10% by weight of binder. The electrode is placed in a vial containing 5 mL of water under stationary conditions for 48 hours. After this time, the electrode is dried at 80° C. under vacuum for 12 hours and then weighed again. The amount of composite compound remaining is then determined. If the polymeric binder does not ensure the mechanical bond of the composite electrode that is its role, the polymer is then considered to be water-soluble. Typically, the polymeric binder is considered to be water-soluble if less than 10% by weight, and preferably less than 1% by weight, of the composite compound remains on the current collector.

[0033] Typically, the shell has a thickness of 500 nm to 8 μm.

[0034] Typically, the composite electrode comprises one or more active materials, one or more binders, and one or more conductive charges.

[0035] Typically, the conductive charge is selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, carbon fibers, carbon nanotubes, graphene pellets, powdered metals such as copper, nickel, aluminum or silver, metal fibers, and any combination thereof.

[0036] In one embodiment, the conductive charge is carbon black.

[0037] Typically, various materials can be used as electrode active materials. Such active materials depend on the type of electrical energy storage device. The active materials typically include O atoms and at least one of the following atoms: cobalt (Co), manganese (Mn), nickel (Ni), aluminum (Al), chromium (Cr), iron (Fe), magnesium (Mg), strontium (Sr), vanadium (V), titanium (Ti), molybdenum (Mo), rare earth metals, copper (Cu), selenium (Se), sulfur (S), phosphorus (P), and silicon (Si).

[0038] Other materials can be used, such as organic active materials, which typically contain O, C and N atoms.

[0039] In one embodiment, the active material is LiFePO 4 or FePO 4 It is.

[0040] In one embodiment, the active material is porous carbon.

[0041] In one embodiment, the organic or metalorganic material is deposited by plasma processing. For example, the metalorganic material is an organosilane, or an organoalane, or a mixture of organic and metalorganic materials in different ratios. Examples of possible precursors of metalorganic materials include divinyltetramethyldisiloxane (DVTMDSO), octamethylcyclotetrasiloxane (OMCATS), hexamethyldisilazane (HMDSN), tetramethyldisiloxane, tetramethylcyclotetrasiloxane, trimethylsilane, organosilicon with methyl and methoxy groups, such as tetramethoxysilane (TMOS), methyltrimethoxysilane (MTMOS), dimethyldimethoxysilane (DMDMOS), trimethylmethoxysilane (TMMOS), hexamethyldisilane, etc. Examples of organic precursors include CxFy or CxFyAz (where A is a heteroatom and x, y, and z represent the number of each atom therein), such as 1-fluoroheptane, 1,7-octadiene, acetylene, methane, propylene, styrene, acrylic acid, and the like.

[0042] Advantageously, to the inventors' knowledge, organosilicon shells on composite electrodes comprising, inter alia, a water-soluble polymer as a binder have not been reported specifically to limit the dissolution of said water-soluble polymer.

[0043] Advantageously, the shell exhibits sufficiently low resistivity to function as a composite electrode shell in an electrical energy storage device, such as a battery.

[0044] Advantageously, said shell represents a variable hydrophobic functionalization of the surface of the composite electrode body, which makes it possible to control the degree of liquid wetting and the interaction of the liquid with the electrode at the electrode / electrolyte interface. The invention advantageously facilitates adaptation to a wide range of liquid compositions.

[0045] Advantageously, said shell has good mechanical properties that enable it to withstand the volume changes induced during electrochemical charging and discharging of the active material.

[0046] Advantageously, the shell exhibits sufficient porosity / morphology to retain mechanical properties and allow exchange of active species between the electrode and the electrolyte.

[0047] In one embodiment, the shell comprises a layer comprising the at least one organic or organometallic material. Typically in this embodiment, this layer is at the surface of a composite electrode.

[0048] In one embodiment, the shell comprises a layer comprising the at least one organic or organometallic material and one or more other layers, in which the layer comprising the at least one organic or organometallic material may or may not be at the surface of the composite electrode.

[0049] In one embodiment, the surface of the composite electrode comprises at least one layer of molecules that functionalize the surface of the composite electrode, in particular to modify the wettability of the surface of the composite electrode and / or its interaction with the surrounding liquid.

[0050] In one embodiment, the organometallic material is deposited by plasma deposition, particularly plasma enhanced chemical vapor deposition (PECVD).

[0051] Preferably, the plasma treatment is carried out at atmospheric pressure.

[0052] In one embodiment, the plasma treatment is carried out at reduced pressure.

[0053] Advantageously, said plasma treatment is carried out at atmospheric pressure in a horizontal geometry (topography of the process).

[0054] In one embodiment, the plasma treatment comprises a dielectric barrier discharge, preferably the dielectric barrier discharge is suitable for processing layered substrates.

[0055] In a preferred embodiment, the plasma treatment is integrated into a roll-to-roll process, which advantageously allows operation in semi-industrial conditions allowing continuous deposition of protective films or layers on reels typically several meters long.

[0056] In one embodiment, the plasma treatment is accomplished at atmospheric pressure using an alternative reactor arrangement (not horizontal).

[0057] Advantageously, said plasma treatment is facilitated by a jet type treatment operated by a mechanical arm.

[0058] Typically, to generate the plasma, a current collector covered with an electrode is placed in a plasma reactor operating at atmospheric or low pressure.

[0059] In one embodiment, to generate the plasma, a carrier gas (typically He, Ar or N 2 ) is a reactive gas (N 2 , N 2 O, O 2 , H 2 , C.H. 4 , C 2 H 6 , C.F. 4 , C 3 F 6 , C 4 F 8 ) and / or with a gas containing at least one organic molecule and / or organometallic molecule in various proportions.

[0060] In one embodiment, the gas includes a compound for a targeted application, such as electrode protection for an organic electrolyte battery.

[0061] Typically, the power supply is adapted to the plasma device being utilized.

[0062] If the plasma treatment is performed at atmospheric pressure, radio frequency, audio frequency, microwave power, or even micro- and nano-pulsed power sources are preferred. If the plasma treatment is performed at low pressure, DC, radio frequency, or microwave power sources are preferred.

[0063] Advantageously, said plasma treatment at atmospheric pressure operates in a homogeneous regime (Townsend discharge, or luminescence / glow) or in a filamentary regime if the energy dissipated through the filament is controlled to control the homogeneity of the treatment without damaging the current collector (e.g. with mechanical treatments).

[0064] Advantageously, the use of filamentary discharges in the mild regime makes it possible to modify the homogeneity of the electrode and / or the shell deposited, in order to influence the final porosity of the composite electrode covered by the shell.

[0065] Typically, the plasma is generated at atmospheric pressure in a controlled mixture of helium and an organosilane or organoalane-linked molecular precursor, such as a polyalkyldisiloxane, e.g., a disiloxane, e.g., hexamethyldisiloxane (HMDSO), 2,4,6,8-tetramethylcyclotetrasiloxane (TMCTS), or tetraethoxysilane (TEOS).

[0066] In one embodiment, the molecular precursor is a fluorine-based molecule, such as CxFy or CxFyAz (where A is a heteroatom, and x, y and z indicate the number of each atom therein), such as 1-fluoroheptane. However, for the purpose of the present invention, it is necessary to avoid environmentally unfriendly materials. Therefore, this embodiment is less preferred. Moreover, such fluorine-based materials will be more difficult to store on an industrial scale.

[0067] Advantageously, the electrical excitation utilized is in the audio frequency range with power control throughout the deposition process.

[0068] Typically, the thickness of the shell varies with processing time.

[0069] In one embodiment, several layers are deposited.

[0070] In one embodiment, layers having different chemistries are deposited.

[0071] Advantageously, the morphology and chemical composition of the shell varies depending on the type of precursor.

[0072] Advantageously, the morphology of the shell (roughness, electrode coating, porosity, thickness) and the chemical nature of the groups present on the surface and in the interior of the shell are parameters that make it possible to optimize the final product.

[0073] Advantageously, said plasma treatment makes it possible to modify the porosity of the shell, advantageously modifying the tortuosity as a function of the porosity, which can affect the ion transport within the membrane.

[0074] Advantageously, said plasma treatment controls the chemistry of the surface and shell volume of the composite electrode, which makes it possible to modify the stability of the thin films produced and thereby to control the degradability of the composite electrode, especially for time-dependent applications. The present invention therefore relates to a time-controlled degradable electrode.

[0075] Advantageously, the use of non-hazardous precursors in the plasma process not only makes it possible to utilize environmentally friendly manufacturing methods, but also to create non-hazardous shells that are difficult to biodegrade and / or can decompose without releasing highly harmful components.

[0076] The present invention also relates to a method for making a composite electrode comprising a body comprising at least one water-soluble polymer, said method comprising depositing a material onto at least a portion of said body of said composite electrode by plasma deposition, in particular plasma enhanced chemical vapour deposition (PECVD).

[0077] Plasma deposition, particularly plasma enhanced chemical vapor deposition (PECVD), is also referred to as plasma processing.

[0078] In particular, the present invention relates to a method comprising depositing at least one organic or organometallic material by said plasma deposition, thereby producing a composite electrode according to the invention.

[0079] Advantageously, said plasma deposition is carried out at atmospheric pressure.

[0080] In one embodiment, the plasma deposition is carried out in the presence of a vapor phase containing a precursor of an organosilane or organoalane bond, for example, the precursor is a polyalkyldisiloxane, such as a disiloxane, for example hexamethyldisiloxane (HMDSO), 2,4,6,8-tetramethylcyclotetrasiloxane (TMCTS), or tetraethoxysilane (TEOS).

[0081] In one embodiment, the plasma deposition is performed according to a roll-to-roll process.

[0082] Advantageously, said plasma treatment is carried out on an electrode working in contact with an organic medium.The invention allows for better control of the behaviour of the electrode / electrolyte interface.

[0083] Advantageously, the plasma treatment takes place directly on the electrode or electrodes, which means easy integration into processing and manufacturing lines, especially in existing industrial processes.

[0084] Typically, the invention involves the deposition of a macroscopically homogeneous shell (also called a thin film or membrane) onto the surface of the body of a composite electrode, which facilitates modifying the composite electrode deposited on the current collector to make it compatible with the chemical working environment.

[0085] Advantageously, said plasma treatment results in the formation of a coating layer (shell) on the surface of the composite electrode, which stabilizes the electrode surface with respect to the bonding of the composite electrode. Advantageously, according to the invention, the composite electrode is stable in contact with an aqueous electrolyte. Without said coating layer, the composite electrode does not have sufficient bonding in the presence of an aqueous electrolyte or aqueous medium, which is typically water.

[0086] Advantageously, the use of aqueous solvents significantly reduces the manufacturing costs of the electrodes. Indeed, organic solvents commonly used with typical binders (NMP solvent with PVDF) represent additional costs in the process due to binder solubilization and due to solvent vapor treatment during electrode drying.

[0087] Advantageously, the shell allows the diffusion of ions and ensures the electrochemical stability of the electrode to ensure operation of the electrical energy storage device.

[0088] Advantageously, the shell improves the mechanical stability of the composite electrode and extends its stability area in aqueous media.

[0089] Advantageously, the shell prevents dissolution of the water-soluble binder and accommodates the mechanical changes that occur during charge-discharge cycling of the electrical energy storage device and the electrodes that can be handled in aqueous media.

[0090] Advantageously, the method is applicable regardless of the electrode active material used, as long as it is compatible in the medium and in the electrochemical working potential range. Advantageously, the method is also applicable regardless of the electrode composition used. Preferably, the method works regardless of the thickness of the composite electrode, as long as the electrode works.

[0091] Typically, the methods do not require the use of a mask to create a membrane that allows the passage of ions.

[0092] In one embodiment, the method includes the use of a mask to define the location of treatment on the electrode.

[0093] The fabrication of the composite electrode body is carried out according to the knowledge of those skilled in the art.

[0094] Preferably, an aqueous solvent, more preferably water, is used as the solvent for the fabrication of the composite electrode body.

[0095] The invention also relates to an electrical energy storage device, said device comprising one or more composite electrodes according to the invention or produced by the method according to the invention.

[0096] In one embodiment, the device comprises an aqueous solution in contact with the composite electrode according to the invention.

[0097] In one embodiment, the device includes at least one aqueous electrolyte.

[0098] In one embodiment, the device includes at least one organic electrolyte.

[0099] In one embodiment, the device is a battery, such as a lithium battery or a lithium ion battery, a sodium ion battery or a multivalent ion battery, such as Mg or Ca, a hybrid battery, such as a hybrid battery using Zn, Li or Na ions, or an alkaline battery. [Brief description of the drawings]

[0100] [Figure 1] FIG. 1 is a schematic diagram of a plasma enhanced chemical vapor deposition (PECVD) setup. [Diagram 2] Different morphologies of the shell are shown depending on the organometallic shell precursor: HMDSO (left), TMCTS (middle) or TEOS (right). [Diagram 3]A / B show contact angle measurements for an uncoated CMC electrode A) and for a CMC electrode B) after coating with a shell according to the invention. C / D show mechanical stability tests of the electrodes in aqueous electrolyte: C) for a CMC electrode 10 seconds after curing, D) for a coated electrode 10 seconds after curing and E) 6 months after curing. [Figure 4] Figure 1 shows measurements of the deposition stability window for a 1 m LiTFSI electrolyte in HO. [Diagram 5] 3 shows galvanostatic curves for organosilicon deposition on different surfaces in 1 m LITFSI electrolyte in H2O up to C / 10. [Figure 6] Coulombic efficiency curves in 1 m LITFSI electrolyte in H2O up to C / 10 are shown as a function of cycle number for an LFP-CMC electrode with a shell obtained by HMDSO plasma deposition. [Figure 7] 3 shows infrared spectra of the surface of the body of a composite electrode using CMC as a binder with and without a shell obtained by HMDSO plasma deposition shell before and after cycling. [Figure 8] Figure 2 shows the impedance curves in 1 m LITFSI electrolyte in H2O as a function of cycle number for an LFP-CMC electrode with a shell obtained by HMDSO plasma deposition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0101] [Example] The following examples of the invention are directed to electrodes and batteries, which represent one type of electrical energy storage device.

[0102] Electrode preparation LifePO 4 (P2 provided by Johnson Matthey) was used as the active material. 4 Also, Lepage et al. 46 The FePO was chemically oxidized using hydrogen peroxide and acetic acid.4 It should be noted that other active materials can be utilized that are stable in the electrochemical stability window in contact with the aqueous electrolyte.

[0103] Electrodes for electrochemical evaluation in aqueous electrolytes were prepared using 84 wt.% of the active material (either LFP or FePO 4 The coating was prepared by combining a 100% ZnO current collector (either 100% or 150% ZnO) with 9 wt. % of carbon black Timcal C65 and 7 wt. % of sodium carboxymethylcellulose (CMC, Mw=90,000 g / mol, provided by Sigma Aldrich 419273) binder predissolved in deionized water. The slurry was mixed for 20 min to homogenize using a Kurabo Mazerustar KK-50S planetary stirrer deaerator and spread onto a 30 μm thick stainless steel foil using the doctor blade technique. The use of stainless steel current collectors (8) avoids the typical corrosion problems observed for Al current collectors in aqueous media with lithium salts. The coating was then dried overnight in an oven under vacuum at 70 °C. For the LFP electrodes, 8 mm disks, FePO 4 For the electrodes, 12 mm disks were cut from the coatings. The larger negative electrode dimensions allowed for balancing the positive electrode capacity and ensured that the limitation was due to the working electrode only.

[0104] Plasma deposition The polymer was deposited in a plane-to-plane dielectric barrier discharge at atmospheric pressure. The experimental setup used in this work has been described in previous research papers (J Profili, O Levasseur, N Naude, C Chaneac, L Stafford, N Gherardi, Influence of the voltage waveform during nanocomposite layer deposition by aerosol-assisted atmospheric pressure Townsend discharge, 7 August 2016, Journal of Applied Physics, Vol. 120, No. 5, pp. 053302, AIP Publishing; Jacopo Profili, Olivier Levasseur, Jean-Bernard Blaisot, Anja Koronai, Luc Stafford, Nicolas Gherardi, Nebulization of nanocolloidal suspensions for the growth of nanocomposite coatings in dielectric barrier discharges, October 2016, Plasma Processes and Polymers, Vol. 13, No. 10, pp. 981-989; Olivier Levasseur, Reetesh Kumar Gangwar, Jacopo Profili, Nicolas Naude, Nicolas Gherardi, Luc Stafford, Influence of substrate outgassing on the plasma properties during wood treatment in He dielectric barrier disharges at atmospheric pressure, August 2017, Plasma Processes and Polymers, Vol. 14, No. 8, pp. 1600172. Briefly, all experiments were performed using helium (He, PURITY Praxair) as the carrier gas.The gas mixture (1) (4.5 SLM He with 120 mg / h HMDSO vapor) was continuously injected from one side of the DBD cell to the outlet (5). A constant atmospheric pressure (1 bar) was provided during the process by gentle pumping of the conduit. The purity of the gas injected during the process was ensured by placing the DBD cell under vacuum in a stainless steel sealed chamber prior to the experiment. The discharge cell consisted of two dielectric plates (3) (Al. 2 O 3 Electrode (2) (silver-platinum paste, area 3 × 3 cm, thickness 635 μm) 2 ) extends to the sides of the alumina surface. The stainless steel substrate inside the electrode disk was placed on the lower dielectric surface between the electrodes (8) with its surface in contact with the discharge area (4). To prevent any separation of the substrate from the electrodes, a metal foil was attached to the lower surface using Kapton® tape on all four sides. It should be noted that this geometry allows handling of the foil and layered substrate and can be easily adapted to a roll-to-roll arrangement for continued processing of the electrode foil.

[0105] The discharge area (4) begins at a distance (7) of approximately 10 mm from the beginning (6) of the substrate.

[0106] A discharge is then ignited in the discharge area (4) by applying a sinusoidal voltage (2 kV, 20 kHz) to the electrodes. The treatment was carried out for 10 minutes under these conditions. The applied voltage and current were measured by a high voltage probe (TEKTRONIX P6015A) and by a wideband current coil (LILCO Ltd. 13W5000), respectively. An oscilloscope (Tektronix DPO5204B) was used to record all voltage and current waveforms and to calculate the dissipated power during deposition.

[0107] Electrode characterization The morphology of the electrodes was observed using a benchtop electron microscope HITACHI TM3030Plus, and cross sections were investigated using a JEOL FE-SEM 7600 Field Emission Gun (FEG) Scanning Electron Microscope (SEM) with an accelerating voltage of 10 kV, a working distance of about 4 mm, and a magnification of 5k-50k. Chemical mapping was performed using Energy Dispersive X-ray Analysis (EDS) to investigate the elemental distribution in the electrodes before and after plasma treatment. The quality of the deposited films was characterized by ATR-FTIR (Vertex 70 (Bruker®) equipped with an Attenuated Total Reflection (ATR) module). To characterize the structural changes caused by the plasma treatment, X-ray diffraction (XRD) patterns of the electrodes before and after deposition were shown using a Bruker D8 Advance with CuKα radiation (λ=1.5406 Å) in the 2θ range 10-60° with a step of 0.02°. The wetting behavior of the different surfaces was measured using a contact angle measurement device (OneAttension Theta, Biolin Scientific). Each surface was characterized by observing the contact angle of a small drop (deionized water, 2 μL volume) gently placed on the surface of the material (sessile drop method). The results were recorded using a video camera device for 300 s after stabilization of the deposit (typically about 7 s) (not affected by evaporation of the liquid).

[0108] Battery assembly and electrochemical measurements The aqueous electrolyte was prepared under air and then N 2 Using O 2 After being degassed from 2 The glove box was filled with Ar and kept in a 1M glove box. The exact amount of LiTFSI (3M) was weighed in the Ar-filled glove box. LiTFSI was then dissolved in a corresponding amount of deionized water to reach a concentration of 1M. The same procedure was followed for the sulfate (Li 2 SO 4 , Na 2 SO 4 and ZnSO 4 (Alfa Aesar)) solution (1 m).

[0109] All cells are N 2 The assembly was carried out in a glove box filled with O 2 is the cycle life of the battery 18 This is detrimental to 2 Care was taken to assemble the cells in the absence of HMDSO. The electrochemical stability of the films was measured using a three-electrode Swagelok cell. The working electrode was a 10 mm stainless steel disk with a 500 nm thick HMDSO film, and the counter and reference electrodes were a 10 mm stainless steel disk and an Ag / AgCl electrode (BaSi inc), respectively. For comparison, the same configuration was utilized with an uncovered stainless steel disk as the working electrode. Cyclic voltammetry was performed from -0.75 to 1.25 V vs. Ag / AgCl, i.e., 2.51 to 4.51 vs. LiTFSI electrolyte, using a sweep rate of 0.5 mV / s. + With sulfate electrolyte, the stability window was -0.50 to 1.00 V vs. Li + Measured in μg / Li.

[0110] For the cycling tests, a two-electrode Swagelok cell was used. GF / D borosilicate glass fiber from Whatman was used as the separator. The electrochemical performance was measured at various current rates from -0.6V to 0.6V vs. LiFePO 4 / FePO 4 (i.e. 2.8V~4.0V vs. Li + The current (I / Li) was determined on the cell. All electrochemical measurements were performed at room temperature using a VMP electrochemical station (Biologic, France). For each sample, two cells were assembled to ensure reproducibility. A capacity variation of less than 1 mAh / g was found for every set of two cells. For impedance measurements, a three-electrode cell was used in the same configuration with an Ag / AgCl reference electrode.

[0111] As a general comment The plasma process according to the invention uses only non-hazardous gases and small amounts of non-hazardous precursors (typically 1-1000 ppm) to produce the shell. The plasma process according to the invention can be generated at atmospheric pressure, which significantly reduces the costs associated with pumping and gas control equipment. The method according to the invention is therefore economical and environmentally friendly.

[0112] The method is highly suitable for processing substrates in the form of flexible, configurable sheets using a variety of power sources, the method is simple to perform and highly compatible with continuous industrial processes. [Explanation of symbols]

[0113] 1 Gas Mixture 2 electrodes 3 Dielectric plate 4 Discharge Area 5 exit 6 The beginning of the board

Claims

1. 1. An electrical energy storage device, the device comprising one or more composite electrodes and at least one aqueous electrolyte, the composite electrode being placed in contact with the aqueous electrolyte, the electrode comprising an electrode body and an electrode shell, the body comprising at least one water soluble polymer, and at least a portion of the shell comprising at least one organic or organometallic material.

2. 2. The device of claim 1, wherein the device is a battery, such as a lithium battery or a lithium ion battery, a sodium ion battery, or a multivalent ion battery, such as Mg or Ca, a hybrid battery, such as a hybrid battery using Zn, Li or Na ions, or an alkaline battery.

3. 3. The device of claim 1 or 2, wherein the water soluble polymer is selected from the group consisting of polysaccharides, polyethylene glycol (PEG), polyoxyethylene (POE), polyvinylpyrrolidone (PVP), polyvinyl alcohol (PVA), polylactic acid (PLA), polyacrylic acid (PAA), polyacrylamide, N-(2-hydroxypropyl)methacrylamide (HPMA), cellulose derivatives, pectin, chitosan, chitosan derivatives, dextran, carrageenan, guar gum, guar gum derivatives, hyaluronic acid (HA), starch or starch derivatives, polyethyloxazoline, and derivatives thereof.

4. 4. The device of claim 1, wherein the water-soluble polymer is selected from the group consisting of hydroxypropyl methylcellulose (HPMC), hydroxypropyl cellulose (HPC), hydroxyethyl cellulose (HEC), carboxymethyl cellulose (CMC), and sodium carboxymethyl cellulose (Na-CMC).

5. 5. A method for preparing a device according to any one of claims 1 to 4, comprising the deposition of an organic or metalorganic material by plasma treatment, for example the metalorganic material being an organosilane, or an organoalane, or a mixture of an organic material and a metalorganic material, for example the precursor of the metalorganic material being a siloxane, for example divinyltetramethyldisiloxane (DVTMDSO), octamethylcyclotetrasiloxane (OMCATS), hexamethyldisilazane (HMDSN), tetramethyldisiloxane, tetramethylcyclotetrasiloxane, trimethylsilane, methyl and methoxy organosilicon, for example tetramethoxysilane (TMOS), methyltrimethoxysilane (MTMOS), dimethyldimethoxysilane (DMDMOS), trimethylmethoxysilane (TMMOS), or hexamethyldisilane.

6. The method of claim 5 , wherein the organometallic material is deposited by plasma deposition.

7. The method of claim 5 or 6, wherein the method includes depositing the material onto at least a portion of the body of the composite electrode by plasma deposition.

8. 8. The method of claim 6 or 7, wherein the plasma deposition is carried out at atmospheric pressure.

9. 9. The method of any one of claims 6 to 8, wherein the plasma deposition is carried out in the presence of a vapor phase comprising a precursor of an organosilane or organoalane bond, e.g., the precursor is a polyalkyldisiloxane, e.g., a disiloxane, e.g., hexamethyldisiloxane (HMDSO), 2,4,6,8-tetramethylcyclotetrasiloxane (TMCTS) or tetraethoxysilane (TEOS).

10. 10. The method according to any one of claims 6 to 9, wherein the plasma deposition is carried out according to a roll-to-roll process.

Citation Information

Patent Citations

  • Electrode and electrochemical device

    JP2018147887A

  • Lithium Battery Electrodes with Ultra-thin Alumina Coatings

    US20120077082A1